The long‐term outcome of patients in the LRF CLL4 trial: the effect of salvage treatment and biological markers in those surviving 10 years. (12th October 2015) - Else, Monica; Wade, Rachel; Oscier, David; Catovsky, Daniel
Summary: With 10+ years follow‐up in the Leukaemia Research Fund (LRF) CLL4 trial, we report the effect of salvage therapy, and the clinical/biological features of the 10‐year survivors treated for chronic lymphocytic leukaemia (CLL). Overall survival (OS) was similar in the three randomized arms. With fludarabine‐plus‐cyclophosphamide (FC), progression‐free survival (PFS) was significantly longer ( P  < 0·0001), but OS after progression significantly shorter, than in the chlorambucil or fludarabine arms ( P  < 0·0001). 614/777 patients progressed; 524 received second‐line and 260 third‐line therapy, with significantly better complete remission (CR) rates compared to first‐line in the chlorambucil arm (7% vs. 13% after second‐, 18% after third‐line), but worse in the FC arm (38% vs. 15% after both second and third‐line). OS 10 years after progression was better after a second‐line CR versus a partial response (36% vs. 16%) and better with FC‐based second‐line therapy (including rituximab in 20%) or a stem cell transplant (28%) versus all other treatments (10%, P  < 0·0001). The 176 (24%) 10‐year survivors tended to be aged <70 years, with a "good risk" prognostic profile, stage A‐progressive, achieving at least one CR, with a first‐line PFS >3 years and receiving ≤2 lines of treatment. In conclusion, clinical/biological features and salvage treatments both influence the long‐term outcome. Second‐line therapies that induce a CR can improve OS in CLL patients.